Economic analysis of up-to-date sour cherry or in Hungary - Apáti, F. (International Journal of Horticultural Science, 2008)
In this study cost-profit analysis is carried out to up-to-date Hungarian sour cherry orchards. These orchards cover only 1 to 3 thousand hectares from the sour cherry territory of 16 thousand hectares. In a many-year-average a yield of 15 tons per hectare may be reached in up-to-date sour cherry orchards cultivated under high standard conditions. Per hectare direct production costs take up of approximately 1000 thousand HUF, from which the major portion (60%) is accounted for the personal cost of harvesting. Regarding the above mentioned average yield and a selling price of 100 HUF per kilogram a revenue of 1 500 thousand HUF may be realized, which results in a per hectare contribution of 500 thousand HUF. To sum up, regarding the present extremely unfavourable selling price only reaching an average yield of 15 to 20 tons per hectare may lead to appropriate profit.